Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

evaluate the indefinite integral. problem below

Calculus1
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

\[\int\limits ( \Theta - \cos ( 1-\Theta) d \Theta \]
1-sin(1-theta)/-1+C =1 +sin(1-theta)+c
use integral subs, let u=(1-Θ)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

oops its I did a mistake there
it should be \[\theta ^{2}/2 + \sin(1-\theta)+\]
if i use subs what do i do after i get du=-1d\[\Theta \] ?
well, i want explain it step by step u = 1-Θ -----> Θ=1-u, right ?
yes
next, u have got u = 1-Θ du = -dΘ or dΘ = - du, right ?
yesss
next, we substitute of them to the original problem : ∫(Θ−cos(1−Θ))dΘ = ∫[(1-u) - cosu] (-du) = ∫[(u-1) + cosu] du, agree ???
yes
ok, just integral all one by one, int u du= ... int -1du= .... int cosu du= .... what u get ????
1/2 u^2 -u + sin u + c ?
yes, correct now, the last step u must substitute back that u = 1-Θ
i end up getting -1/2 -1/2theta^2 + sin (1-theta) is the -1/2 suppose to be there?
from ur answer : 1/2 u^2 -u + sin u + c , just change u=1-Θ, gives 1/2(1-Θ)^2 -(1-Θ) + sin(1-Θ) + c i think enough be the answer, but if u want simplify it might too
whats the final answer if you simplify?
1/2(1-Θ)^2 -(1-Θ) + sin(1-Θ) + c = 1/2 (1-2Θ + Θ^2) -1 + Θ + sin(1-Θ) + c = 1/2 - Θ +1/2*Θ^2 -1 + Θ + sin(1-Θ) + c = -1/2 +1/2*Θ^2 + sin(1-Θ) + c = -1/2 (1-Θ^2) + sin(1-Θ) + c

Not the answer you are looking for?

Search for more explanations.

Ask your own question